Sono-Assisted Alkali and Dilute Acid Pretreatment of Phragmites karka (Tall Reed Grass) to Enhance Enzymatic Digestibility for Bioethanol Conversion - Ummalyma, Sabeela Beevi; Sahoo, Dinabandhu; Pudiyamadam, Anoop; Adarsh, Velayudhanpillai Prasannakumari; Sukumaran, Rajeev K.; Bhaskar, Thallada; Parida, Ajay (Frontiers in Energy Research, 2021)
Phragmites is the tallest energy crop found as an invasive species worldwide and considered as waste biomass. The present study evaluated the potential of the aquatic biomass Phragmites karka grown from two different lakes as feedstock for biofuel production. A comparative study of biomass was conducted from Chilika Lake and Loktak Lake, India. The methodology involves dilute acid, sono-assisted alkali pretreatment, and hydrolyzed biomass with commercial cellulase. SEM, XRD, and FTIR analysis were performed for the biomass physicochemical studies and confirmed that alterations occurred in the biomass structure, assisting the hydrolysis process. The enzymatic hydrolysis result showed that the highest of reducing sugar yield of 79% was obtained from biomass loading of 10% and 1% w/v alkali with a sonication frequency of 20 kHz for 25 min. Acid pretreatment released maximal reducing sugar yield of 73% attained from biomass loading of 20% and 0.5% w/v acid. Composition analysis of biomass showed that cellulose content increased from 36% to 46%. Sono-assisted alkali pretreatment solubilized 40% of lignin content compared to untreated biomass. Final ethanol recovery from the biomass is 78% fermentation efficiency from glucose. The data indicate that exploiting tall reed grass as a bioenergy raw material can be a viable approach for sustainable utilization of invasive grass/waste biomass for biorefineries, which helps control invasive weeds and management of waste.